Intracellular uptake of nanocrystals: Probing with aggregation-induced emission of fluorescence and kinetic modeling - Jifen Zhang; Clairissa D. Corpstein; Tonglei Li (Elsevier, 2021)
Nanocrystal formulations have been explored to deliver poorly water-soluble drug molecules. Despite various studies of nanocrystal formulation and delivery, much more understanding needs to be gained into absorption mechanisms and kinetics of drug nanocrystals at various levels, ranging from cells to tissues and to the whole body. In this study, nanocrystals of tetrakis (4-hydroxyphenyl) ethylene (THPE) with an aggregation-induced emission (AIE) property was used as a model to explore intracellular absorption mechanism and dissolution kinetics of nanocrystals. Cellular uptake studies were conducted with KB cells and characterized by confocal microscopy, flow cytometry, and quantitative analyses. The results suggested that THPE nanocrystals could be taken up by KB cells directly, as well as in the form of dissolved molecules. The cellular uptake was found to be concentration- and time-dependent. In addition, the intracellular THPE also could be exocytosed from cells in forms of dissolved molecules and nanocrystals. Kinetic modeling was conducted to further understand the cellular mechanism of THPE nanocrystals based on first-order ordinary differential equations (ODEs). By fitting the kinetic model against experimental measurements, it was found that the initial nanocrystal concentration had a great influence on the dynamic process of dissolution, cellular uptake, and exocytosis of THPE nanocrystals. As the nanocrystal concentration increased in the culture media, dissolution of endocytosed nanocrystals became enhanced, subsequently driving the efflux of THPE molecules from cells.